1985
DOI: 10.1073/pnas.82.20.6908
|View full text |Cite
|
Sign up to set email alerts
|

Multiple forms of tubulin in the cilia and cytoplasm of Tetrahymena thermophila.

Abstract: Most higher eukaryotic tubulins are separated into a-and J3-tubulin when electrophoresed in NaDodSO4-denaturing gels, while many lower eukaryotic tubulins are poorly resolved under these conditions, which include a stacking gel (pH 6.80) and a separating gel (pH 8.80). By lowering the pH of the separating gel to 8.25, we have found that tubulin isolated from the protozoan Tetrahymena thermophila is resolved by one-dimensional polyacrylamide gel electrophoresis into two a-tubulins and one P-tubulin. Moreover, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 63 publications
(53 reference statements)
4
31
0
Order By: Relevance
“…Immunoblot analysis was used to verify the specificity of this antibody. The migration profiles of Tetrahymena ␣-tubulin and ␤-tubulin on SDS-PAGE are considerably different from those of mammalian or avian tubulin; mobility of ␣-tubulin in Tetrahymena is faster than that of ␤-tubulin [Suprenant et al, 1985]. The monoclonal antibody against chick ␣-tubulin recognized a single band on a Western blot containing total or ciliary proteins of T. pyriformis, corresponding to ␣-tubulin (Fig.…”
Section: Intramacronuclear Microtubules Undergo Dramatic Reorganizatimentioning
confidence: 96%
“…Immunoblot analysis was used to verify the specificity of this antibody. The migration profiles of Tetrahymena ␣-tubulin and ␤-tubulin on SDS-PAGE are considerably different from those of mammalian or avian tubulin; mobility of ␣-tubulin in Tetrahymena is faster than that of ␤-tubulin [Suprenant et al, 1985]. The monoclonal antibody against chick ␣-tubulin recognized a single band on a Western blot containing total or ciliary proteins of T. pyriformis, corresponding to ␣-tubulin (Fig.…”
Section: Intramacronuclear Microtubules Undergo Dramatic Reorganizatimentioning
confidence: 96%
“…1). Note that, under conditions described under "Materials and Methods," ciliate ␣-tubulins migrate faster than ␤-tubulins (24). Noticeably, a striking difference in reactivity with the anti-glutamylated tubulin mAb, GT335, indicated the presence of a higher level of glutamylation in Tetrahymena than in Paramecium (Fig.…”
Section: Post-translational Modifications Of Axonemal Tubulins Ofmentioning
confidence: 99%
“…In these highly differentiated cells, the microtubular networks are involved in nuclear divisions, intracellular transport, organelle positioning, and are associated with specialized organelles that function in osmotic regulation, feeding, excretion, and locomotion. The ␣-and ␤-tubulins of ciliates are biochemically heterogeneous (17,20,24), suggesting that structural differences among tubulin isoforms are important in generating functionally distinct types of microtubules in a single cell. However, genetic and biochemical studies showed that in ciliates only one or two gene isotypes of ␣-and ␤-tubulin form the bulk of microtubules (6,(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Proteins were separated by SDS-PAGE on 10% polyacrylamide minigels (Laemmli, 1970), containing 0.1% (wt/wt) SDS (99% pure; BDH, Poole, United Kingdom) at pH 8.3, according to Suprenant et al (1985). Under these conditions, Paramecium ␣-tubulin migrates faster than ␤-tubulin.…”
Section: Gel Electrophoresis and Immunoblottingmentioning
confidence: 99%